A Hexabenzocoronene‐Based Helical Nanographene. Issue 45 (10th July 2020) - Martin, Max M.; Hampel, Frank; Jux, Norbert
Abstract: A synthetic route towards a novel hexabenzocoronene‐based helical nanographene motif was developed. A hexaphenylbenzene precursor was therefore designed, which cannot undergo, due to steric restrictions, a complete planarization reaction. This precursor was transformed under oxidative cyclodehydrogenation conditions to a π‐extended [5]helicene, which was fully characterized including X‐ray diffraction analysis. Abstract : A twisted nanographene that is based on the well‐established hexabenzocoronene motif is presented. A [5]helical unit was implemented into the nanographene structure with the help of steric repulsive effects. The π‐extended helicene was characterized by UV/Vis absorption and emission spectroscopy as well as X‐ray crystallography.